The use of herbs according to the perspective of traditional Malay medicine in Selangor, Malaysia - Abdul Aziz, Muhammad Hannan; Mohd Yusoff, Ahmad Nasir; Magima, Mohamad Maulana (Human Resource Management Academic Research Society, 2023)
Herbal medicines have long been a cornerstone of conventional medicine and remain widely used today. In Malay traditional medicine, herbs are the primary component that are usually used to treat various ailments. However, there is still confusion among some Malaysians regarding the functions and benefits of traditional medicine such as herbs as treatment option, most probably due to limited information on the application of herbs in treating diseases. Hence, this study aims to identify the types of herbs used as well as the factors of herbal usage in the Central Zone of Selangor. To obtain such data, a qualitative research methodology was adopted, involving literature review, distribution of surveys to 327 respondents and interviews of several respondents. The study's findings provide relevant information on the various types of herbs used in Selangor as well as their applicability in treating various diseases. This study conclusively supports the efficacy of traditional Malay herbal remedies in treating diverse diseases prevalent in Selangor. Amidst globalization, it is vital for society to earnestly embrace herbal usage for fostering a healthy and thriving life. The study's findings offer valuable insights into the effective utilization of herbs as alternative treatments, complementing modern therapies by the Ministry of Health Malaysia. Embracing this knowledge can pave the way for a comprehensive and holistic approach to healthcare, benefiting the community at large.